2018
DOI: 10.2981/wlb.00404
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and performance of low‐feature GPS collars deployed on bison Bison bison and caribou Rangifer tarandus

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…The performance of the devices was evaluated using similar measures to Jung et al (). Overall performance was taken from deployment success rate, measuring how many devices were working on deployment, and the early failure rate, measuring how many of the devices stopped collecting data earlier than expected.…”
Section: Description and Implementationmentioning
confidence: 99%
See 3 more Smart Citations
“…The performance of the devices was evaluated using similar measures to Jung et al (). Overall performance was taken from deployment success rate, measuring how many devices were working on deployment, and the early failure rate, measuring how many of the devices stopped collecting data earlier than expected.…”
Section: Description and Implementationmentioning
confidence: 99%
“…A comparison of commercially available collars deployed on Australian mammals by Matthews et al () found that 48.6% of collars deployed failed early, with 30% of collars having intermittent failures during deployment. However, Jung et al () had an 89% overall deployment success rate on over 100 collars of a single brand and type deployed. Collins, Petersen, Carr, and Pielstick () compared custom devices to commercial devices where their custom devices had a high failure rate (7/8) which suggests that the devices trialled here may be more reliable than other custom devices but does highlight the risk that could occur with custom devices.…”
Section: Description and Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…tracking device can record the longitude and latitude directly with high accuracy (<10 m) 19 , particularly in an open landscape 20,21 and/or with more satellites 21 . Thus, this system allowed us to delineate the whole migration route and to track fine-scale habitat use during the migration period.…”
mentioning
confidence: 99%